Detection of Tuberculosis Cases Among Correctional Facility Inmates in Indonesia - Karlinda, Amelia Yuri; Syarif, Syahrizal (The Indonesian Journal of Infectious Diseases, 2025)
Background: Tuberculosis (TB) remains a major health burden in correctional facilities, with incidence rates significantly higher than in the general population due to confined and overcrowded environments. Systematic screening is an essential approach to detecting TB cases early; however, national data on the effectiveness of systematic screening in Indonesian correctional facilities remains limited. Methods: This cross-sectional study utilized data from TB screening of 206,337 inmates across 376 correctional facilities in Indonesia conducted between July and December 2023. Screening included symptom assessment and chest X-ray (CXR) examination, followed by rapid molecular testing (TCM) for suspected cases. Analysis was performed to evaluate the proportion of TB case detection and the association between screening results and TB diagnosis. Results: A total of 4,881 TB cases were identified, with a detection proportion of 2.37% and a prevalence rate of 2,369 per 100,000 inmates. Systematic use of CXR successfully identified TB cases, including among asymptomatic inmates, with 25.99% of inmates showing abnormal CXR findings confirmed to have TB. There was a statistically significant association between CXR results and TB case detection (p < 0.001). Conclusion: Systematic screening combining symptom assessment, CXR, and TCM is effective in enhancing early TB case detection in correctional facilities. These findings reinforce the need for widespread implementation of comprehensive screening strategies, strengthening of healthcare services, and infection control measures to reduce the TB burden in Indonesian correctional settings.